Development of a Metabolite Sensor for High-Throughput Detection of Aldehydes in Escherichia Coli - Frazão, Cláudio R.; Maton, Victor; François, Jean M.; Walther, Thomas (Frontiers in Bioengineering and Biotechnology, 2018)
We have developed a fluorescence-based metabolite sensor enabling in vivo detection of various aldehydes of biotechnological interest in Escherichia coli. YqhC is a transcriptional regulator that is known to be involved in the upregulation of the yqhD-dgkA operon in the presence of aldehydes. We took advantage of this property by constructing a bi-modular biosensor, in which a sensing module constitutively expresses yqhC while a reporter module drives the expression of the syfp2 reporter gene that is put under control of the yqhD promoter. The sensitivity of the sensor has been optimized by engineering the 5’-UTRs of both the sensing and the reporter modules resulting in a 70-fold gain of fluorescence in response to the model compound glycolaldehyde at 5 mM. The optimized sensor further responded to other aldehydes when supplemented to the cultivation medium at concentrations of 1 – 10 mM. We furthermore showed that this metabolite sensor was functional in vivo as it responded to the presence of glycoladehyde that is specifically produced upon induction of a synthetic xylulose-1-phosphate pathway expressed in E coli. This bi-modular sensor can therefore be employed as an exquisite tool for FACS-based ultra-high-throughput screening of aldehyde (over) producing enzymes.